Implementation of Project-Based Learning Model in Islamic Religious Education for Grade X at Muhammadiyah Senior High School 1 Surakarta - Pratama, Dhaifullah Mochtar Adi; Abidin, Zaenal (Universitas Islam Negeri Sumatera Utara, 2024)
A learning model is an approach to change learners' behavior adaptively or generatively, which is strongly related to learners' learning styles and teachers' teaching styles. One prominent learning model is Project-Based Learning (project based learning), where students actively participate in real projects to solve real-world problems independently. This research focuses on the implementation of project based learning in Islamic Religious Education (PAI), which aims to develop learners' religious values and character. This research uses a phenomenological approach to describe the situation in the field and understand individual experiences in the context of everyday life. Through direct data collection in the field, this study reveals how project based learning in Islamic Education affects the development of students' social skills, creativity, and concept understanding. The results show that project based learning not only improves students' academic understanding, but also builds inclusive character and effective communication skills in group collaboration. In conclusion, project based learning in Islamic Religious Education makes a positive contribution to education by combining religious values with project-based learning. By going in-depth, this study hopes to provide useful insights for future educational development, particularly in the context of relevant and empowering religious teaching.